Introducing IsoMad, a compilation of isotopic datasets for Madagascar - Hixon, Sean W; Fernandes, Ricardo; Andriamahaihavana, Antonin; Baden, Andrea L; Blanco, Marina B; Caulier, Guillaume; Dammhahn, Melanie; Eeckhaut, Igor; Eppley, Timothy M; Frédérich, Bruno; Ganzhorn, Jörg U; Garbaras, Andrius; et al. (Scientific data, 2024)
We present the first open-access, island-wide isotopic database (IsoMad) for modern biologically relevant materials collected on Madagascar within the past 150 years from both terrestrial and nearshore marine environments. Isotopic research on the island has increasingly helped with biological studies of endemic organisms, including evaluating foraging niches and investigating factors that affect the spatial distribution and abundance of species. The IsoMad database should facilitate future work by making it easy for researchers to access existing data (even for those who are relatively unfamiliar with the literature) and identify both research gaps and opportunities for using various isotope systems to answer research questions. We also hope that this database will encourage full data reporting in future publications.
Keywords: izotopy dusíku; Nitrogen Isotopes; Databases, Factual; Madagaskar; Carbon Isotopes; izotopy uhlíku; Madagascar; databáze faktografické; Animals; zvířata